Faktor Penentu yang Mempengaruhi pada Keputusan Pembeliaan Smartphone: Studi Empiris Kabupaten Lampung Timur - Buchori Buchori; Evi Novitasari; Rinnanik Rinnanik; Wulandari Wulandari (Komunitas Dosen Indonesia, 2022)
Purchase decisions are strongly influenced by several factors. The purposes of this study focus on examining two crucial factors in purchasing decisions, which are promotion and location on Smartphone purchase. Respondents in this study are consumers from East Lampung Regency. Using statistics analysis study by multiple linear regression, this study proved that promotion and location have a significant effect on smartphone purchase decisions of the consumers. Strategically accessible locations and good promotions in fact will be increasing the purchase of Smartphone products at East Lampung Regency. This study also revealed that consumers have the same views and perceptions of products in the area.